High-Frequency Ripple Injection Signals for the Effective Utilization of Residential EV Storage in Future Power Grids With Rooftop PV System - Muttaqi K.M.; Rahman O.; Sutanto D.; Hossain Lipu M.S.; Abdolrasol M.G.M.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Electric control equipment; Electric load flow; Electric load management; Electric machine control; Electric power system control; Electric power transmission networks; Electric substations; Electric vehicles; Secondary batteries; Stochastic systems; Audio frequencies; Audio frequency injection control signal; Charging station; Control signal; Electric vehicle charging; EV Charging; EV charging station; Load control; Load modeling; Ripple injection signal; Substation; Vehicle to grids; Vehicle-to-grid